Tribocorrosion behaviour of anodic treated titanium surfaces intended for dental implants - Alves, A. C.; Oliveira, F.; Wenger, F.; Ponthiaux, P.; Celis, J. P.; Rocha, Luís Augusto Sousa Marques da [UNESP] (IOP Publishing, 2013)
Tribocorrosion plays an important role in the lifetime of metallic implants. Once implanted, biomaterials are subjected to micro-movements in aggressive biological fluids. Titanium is widely used as an implant material because it spontaneously forms a compact and protective nanometric thick oxide layer, mainly TiO2, in ambient air. That layer provides good corrosion resistance, and very low toxicity, but its low wear resistance is a concern. In this work, an anodizing treatment was performed on commercial pure titanium to form a homogeneous thick oxide surface layer in order to provide bioactivity and improve the biological, chemical and mechanical properties. Anodizing was performed in an electrolyte containing β-glycerophosphate and calcium acetate. The influence of the calcium acetate content on the tribocorrosion behaviour of the anodized material was studied. The concentration of calcium acetate in the electrolyte was found to largely affect the crystallographic structure of the resulting oxide layer. Better tribocorrosion behaviour was noticed on increasing the calcium acetate concentration. © 2013 IOP Publishing Ltd.
Keywords: Anodized material; Anodizing treatment; Biological fluids; Commercial pure titanium; Crystallographic structure; Implant materials; Metallic implants; Titanium surfaces; Biological materials; Corrosion resistance; Dental prostheses; Electrolytes; Mechanical properties; Phospholipids; Titanium; Titanium oxides